Perylenediimide derivatives based on a dendritic oligothiophene core as electron acceptor for use in polymer solar cells. (April 2017) - Yi, Maoheng; Yi, Jinduo; Wang, Junkai; Wang, Lilei; Gao, Wei; Lin, Yi; Luo, Qun; Tan, Hongwei; Ma, Chang-Qi; Wang, Hongyu
Abstract: Two perylenediimide derivatives (3T-PDI2 and 6T-PDI4 ) based on dendritic terthiophene (3T) and sexithiophene (6T) cores were designed and synthesized. The rigid and dendritic oligothiophene core ensures a non-planar structure of these two compounds, which was confirmed by theoretical molecular structure simulation. The optical and electrochemical investigation results showed that both compounds have similar LUMO energy level of −4.1 eV, demonstrating that the LUMO orbital is mainly localized on the PDI moiety. Polymer solar cells using 3T-PDI2 and 6T-PDI4 as the electron acceptor, and PTB7-Th as the donor were fabricated and tested. A power conversion efficiency (PCE) of 4.12% was obtained for the 6T-PDI4 based device, which is higher than that of 3T-PDI2 based device (3.41%). Higher charge carrier mobility and less Shockley-Read-Hall recombination were also measured for the 6T-PDI4 based device. The current work demonstrates that dendritic PDI derivatives could serve as non-fullerene acceptor for use in polymer solar cells. Graphical abstract: Highlights: Two branched oligothiophene cored PDI derivatives were synthesis. These PDIs showed similar LUMO energy levels to PC61 BM. The bigger molecule 6T-PDI4 showed better device performance over 3T-PDI2 . Higher charge carrier mobility and less SRH recombination was found for 6T-PDI4 .